Route towards complete 3D hydro-chemical simulations of companion-perturbed AGB outflows. Issue Volume 16:Issue S366(2020) (November 2020) - Maes, Silke; Siess, Lionel; Homan, Ward; Malfait, Jolien; De Ceuster, Frederik; Ceulemans, Thomas; Donné, Dion; Esseldeurs, Mats; Decin, Leen
Abstract: Low- and intermediate mass stars experience a significant mass loss during the last phases of their evolution, which obscures them in a vast, dusty envelope. Although it has long been thought this envelope is generally spherically symmetric in shape, recent high-resolution observations find that most of these stars exhibit complex and asymmetrical morphologies, most likely resulting from binary interaction. In order to improve our understanding about these systems, theoretical studies are needed in the form of numerical simulations. Currently, a handful of simulations exist, albeit they mainly focus on the hydrodynamics of the outflow. Hence, we here present the pathway to more detailed and accurate modelling of companion-perturbed outflows with, by discussing the missing but crucial physical and chemical processes. With these state-of-the-art simulations we aim to make a direct comparison with observations to unveil the true identity on the embedded systems.